1987
DOI: 10.1002/chin.198734138
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ESR Study on the σ‐ and π‐Radical Cations Formed by One‐Electron Oxidation of Phenyldiazomethanes.

Abstract: 138ChemInform Abstract The radical cations from (I) and (II) obtained during electrochemical oxidation at low temp. seem to have a "σ-radical" structure, in which an unpaired electron is localized on two nitrogens. The half-life of (I) (R: -Ph) is about 10s at -33 rc C and 90s at -83 rc C. The radical cations derived from (III), however, have clearly a "π-radical" structure, the spin density being delocalized on both diazo and phenyl groups. These radical cations are relatively stable with half-lives of ca. 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Because of the vigorous N 2 evolution and high efficiencies of these reactions, few studies have reported such radicals 20 21 22 23 . The EPR signals of some diazo radical cations of diphenyldiazomethanes and their derivatives have been recorded after electrochemical oxidation or irradiation in Freon matrices 24 25 26 . In frozen toluene at 40 K, a carbon-centered Co-carbene radical was detected by EPR spectroscopy, along with several other paramagnetic cobalt species 17 , which complicated the spectral analysis.…”
mentioning
confidence: 99%
“…Because of the vigorous N 2 evolution and high efficiencies of these reactions, few studies have reported such radicals 20 21 22 23 . The EPR signals of some diazo radical cations of diphenyldiazomethanes and their derivatives have been recorded after electrochemical oxidation or irradiation in Freon matrices 24 25 26 . In frozen toluene at 40 K, a carbon-centered Co-carbene radical was detected by EPR spectroscopy, along with several other paramagnetic cobalt species 17 , which complicated the spectral analysis.…”
mentioning
confidence: 99%